Sistem Informasi Manajemen Data Kecelakaan Lalu Lintas Berbasis Web di Kepolisian Resor Kota Surakarta - Muhammad Fauzi; Ari Pantjarani; Mursid Dwi Hastomo (Politeknik Harapan Bangsa Surakarta, 2024)
Traffic accidents are a serious problem that can result in loss of life, serious injuries, and property damage. Polresta Surakarta, as a law enforcement agency, is responsible for handling traffic accident cases in its jurisdiction. However, there are still challenges in managing accurate, integrated, and easily accessible accident data. Manual recording and lack of efficient information systems can hinder the collection, analysis, and reporting of accident data needed for informed decision-making. The objective of this research is to design and implement an efficient and effective web-based traffic accident data information system at Polresta Surakarta. The author utilizes the SDLC (System Development Life Cycle) waterfall model with web-based system development. The information system will be designed and implemented using PHP and MySQL as the database. Based on the research results, it can be concluded that the traffic accident data information system at Polresta Surakarta can be designed and implemented based on the web.